2017
DOI: 10.1186/s12904-017-0187-y
|View full text |Cite
|
Sign up to set email alerts
|

Critical attitudes and beliefs towards guidelines amongst palliative care professionals – results from a national survey

Abstract: BackgroundLittle is known about palliative care professionals’ attitudes towards guidelines. In 2015, the German Association for Palliative Medicine (DGP) published an evidence based guideline for palliative care in adults with incurable cancer. Before publication we conducted a national survey among members of the DGP to detect possible barriers and facilitators for its implementation. The aim of the present publication was to evaluate critical attitudes and beliefs which could hinder the effective implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
0
14
0
1
Order By: Relevance
“…54 Although developing guidelines could be an important instrument in improving clinical practice, the mere development of these guidelines will not directly lead to better outcomes unless they are successfully implemented into routine practice. 5557 From the included studies we could not always verify how these guidelines and protocols were developed and more importantly how they were implemented in daily clinical practice. In their study Kalies and colleagues 55 identified attitudes and beliefs amongst palliative care professionals which could hinder the effective implementation and impact of guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Although developing guidelines could be an important instrument in improving clinical practice, the mere development of these guidelines will not directly lead to better outcomes unless they are successfully implemented into routine practice. 5557 From the included studies we could not always verify how these guidelines and protocols were developed and more importantly how they were implemented in daily clinical practice. In their study Kalies and colleagues 55 identified attitudes and beliefs amongst palliative care professionals which could hinder the effective implementation and impact of guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…5557 From the included studies we could not always verify how these guidelines and protocols were developed and more importantly how they were implemented in daily clinical practice. In their study Kalies and colleagues 55 identified attitudes and beliefs amongst palliative care professionals which could hinder the effective implementation and impact of guidelines. Scepticism regarding the quality of existing guidelines was high and many believed that guidelines could restrict the flexibility of individual patient care.…”
Section: Discussionmentioning
confidence: 99%
“…This could partly be explained by MDs having procedures for discussing difficult issues with colleagues and the multidisciplinary team and rating this collaboration as being more favourable than RNs . Moreover, support from colleagues has been identified as a main contributory factor for MDs' resilience . This could also explain why, in a Swedish paediatric oncology study, MDs had a significantly lower total moral distress score compared with RNs …”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, support from colleagues has been identified as a main contributory factor for MDs' resilience. 19 This could also explain why, in a Swedish paediatric oncology study, MDs had a significantly lower total moral distress score compared with RNs. 20 The only significant difference identified between years of experience was that NAs with less than 5 years of experience scored higher on the item on "guidelines help me" than NAs with more experience.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the evaluation of the significance of different SOPs for different symptoms, the weighting of different symptoms was also analyzed in an online study. A focus on certain symptoms such as respiratory distress and pain became apparent [32,33]. The main topics of the SOPs may be identified not only in the S3 guideline on palliative medicine, but also in the ASCO [34] and the NCCN guidelines [35].…”
Section: Discussionmentioning
confidence: 99%